2015
DOI: 10.1148/radiol.15141905
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MR Imaging with High-Resolution Dynamic Contrast-enhanced and Diffusion-weighted Imaging at 7 T Improves the Assessment of Breast Tumors: A Feasibility Study

Abstract: The clinical use of 7-T multiparametric MR imaging is feasible, provides good or excellent image quality, and has the potential to improve diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 34 publications
9
47
0
1
Order By: Relevance
“…However, this provides mainly morphologic, and, to some extent, functional information . To improve specificity, reduce false‐positive findings, and facilitate an improved response assessment to neoadjuvant treatment, the concept of mpMRI has recently been extended to breast imaging . Multiparametric imaging of the breast aims to simultaneously quantify and visualize multiple functional processes at the cellular and molecular levels to further elucidate the development and progression of breast cancer and the response to treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this provides mainly morphologic, and, to some extent, functional information . To improve specificity, reduce false‐positive findings, and facilitate an improved response assessment to neoadjuvant treatment, the concept of mpMRI has recently been extended to breast imaging . Multiparametric imaging of the breast aims to simultaneously quantify and visualize multiple functional processes at the cellular and molecular levels to further elucidate the development and progression of breast cancer and the response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several functional MRI techniques have been assessed for the multiparametric imaging of breast tumors. There is evidence that multiparametric imaging, using different functional MRI parameters, provides detailed information about the hallmarks of cancer, including neoangiogenesis, cellularity, tumor microenvironment, metabolite concentration, receptor status, tissue pH, and oxygenation, which cannot be obtained with a single parameter, such as CE‐MRI alone, and thus, improves diagnostic accuracy and assessment of response to neoadjuvant therapy . This article will first introduce current parameters obtained from CE‐MRI, diffusion‐weighted imaging (DWI), and proton magnetic resonance spectroscopy ( 1 H‐MRSI) for breast MRI at 3T and 7T.…”
Section: Introductionmentioning
confidence: 99%
“…These properties have been attributed to higher cellularity and reduced extracellular matrix in cancers and may allow for improved detection of tumors and for assessment and differentiation between malignant and benign tumors. DWI has been shown to improve the diagnostic accuracy of conventional breast MRI in combination with dynamic contrast enhanced MRI (DCE‐MRI), and has potential to assist in treatment response prediction …”
mentioning
confidence: 99%
“…A sensitivity of 100%, specificity of 88.2%, has been claimed for a combination of DW-MRI + DCE-MRI, which was greater than for individual parameters (DCE-MRI 100%/53.2%; DW-MRI 93.1%/88.2%) such that it eliminated all false-negative findings and reduced false-positive findings. 124 The addition of 31 P-MRS in a small (n = 15) study by another group showed an inverse relationship between ADC and tumor grade. A relative increase of PME over phosphodiester (PDE) showed significant association with increasing mitotic counts.…”
Section: Value Of Mpmri In Clinical Decision-makingmentioning
confidence: 94%